PENGEMBANGAN SISTEM PENGELOLAAN PUBLIKASI DOKUMEN MAHASISWA STTH MEDAN BERBASIS CLOUD COMPUTING - Muhammad Yopi Ramadhan Siregar; Fajrillah (Department of Science and Technology Ibrahimy University, 2016)
Publication of the document Informatics Engineering Program Technical High School Hope Terrain basically still manual, where the student to see hardcopy documents must visit the library while to get the softcopy documents students must consent in advance to the department office staff to get it. Due to it is not very effective and efficient in this study the authors make the publication of a document management system development STTH students Medan based cloud computing. Where the purpose of the development of such systems to help present the students with information process documents quickly, easily and efficiently, and increase student satisfaction STTH Medan in lectures. In the implementation of this system was built and designed using the programming language PHP and using MySQL database.